Heuristic Evaluation on Interface of Thesis Management Information System in Vocational Environment - Thamrin, Thamrin; Ambiyar, Ambiyar; Simatupang, Wakhinuddin; Wahyudi, Rido (Universitas Negeri Padang, 2023)
In this study, we used Nielsen's heuristics to analyze the user interface of a thesis management information system in the vocational education environment. This system environment is designed to assist students in managing and organizing all processes related to thesis writing. The main framework in this study is Nielsen's heuristics, supplemented with experiments to evaluate the extent to which the user interface of the system meets user preferences (user-friendly). The population involved in this research consists of faculty members and students, with a sample size of 50 individuals. Analysis and discussion were conducted through the distribution of questionnaires to the participants. Based on the research findings, it was discovered that the Visibility of system status achieved a score of 163.5. Overall, this study concludes that the thesis management information system in the vocational education environment that we developed successfully achieves its main objective by having a user-friendly interface.